Regionalisation in a global economy some lessons from the European experience - Heinz Gert Preuße (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 1997)
In this paper, I will discuss this question with special emphasis on the European experience. The European Union (EU) qualifies for an interesting case study because of two reasons. First, it has been founded more than 40 years ago in 1957. Second, its ongoing process of deep Integration is appropriate to demonstrate quite different (positive and negative) aspects of regionalisation. In order to analyse the European case, it is necessary to take into account the changing international economic environment, that is, globalisation. Following this line of reasoning, the paper will be organised as follows: First, I shall highlight some central features of globalisation. Second, I will analyse whether the EU can be considered a successful economic group of "open regionalisation". This analysis also tackles the question if Europe (the European Union) has become a "fortress". The widely held belief outside Europe, that the European Union has indeed become an inward looking region had considerable impact on the formation of NAFTA, APEC, MERCOSUR and other new Integration areas. On top of that, it will be of considerable importance in the future. Finally, I shall draw some conclusions for regional policies elsewhere.
Keywords: 330; Regionale Wirtschaftsintegration; Globalisierung; Wirtschaftsintegration; EU-Staaten; Welt